In defense of undeservedly accused and offended medical doctors: "Medical Doctor's Rights", а 3rd edition review - A. S. Shkoda; D. V. Blinov; A. D. Makatsariya (IRBIS LLC, 2020)
Currently, a number of court hearings regarding potential crimes in delivering health-care services have been exponentially increased. Some of them receive publicity and launch public debates, but many more of those stay beyond the information field. A number of medical doctors are targeted in the investigation as defendants and sentence to actual jail time. Numerous medical workers envisioning a threat to their professional carrier, and even freedom, may now avoid of risky manipulations and interventions, which may eventually negatively affect patient's prognosis. In such situation, increasing awareness about rights of medical workers acquires special relevance. In the mean time, professional publications dedicated to this topic are sharply demanded that might be useful and written in plain Russian. Among them, it may be highlighted a book "Medical Doctor's Rights", by A.A. Ponkina and I.V. Ponkin thoroughly elucidating professional rights and providing tools necessary for their defense. Although we believe that it's scarcely describes causes, real-life cases it is excusable for this otherwise brilliant book. We recommend it for careful examination both for law enforcement officers involved in such lawsuits and a wide audience of healthcare workers as well as medical students.